Formulasi Gel Ekstrak Buah Tomat (Solanum lycopersicum L.) dengan Variasi Konsentrasi HPMC serta Uji Fisiknya - Ilmiyah Setiani; Nur Cholis Endriyatno (Jurusan Farmasi Universitas Negeri Gorontalo, 2023)
Tomato (Solanum lycopersicum L.) has sunscreen activity because it contains flavonoids and lycopene. At a concentration of 10% tomato fruit extract is photoprotection. Gels can increase the effectiveness and comfort in its use. HPMC selected gelling agent because it produces good physical properties. The purpose of this study was to determine the effect of the concentration of HPMC as a gelling agent on physical properties and formulate a gel preparation of tomato fruit extract. This type of research is experimental, made of three formulas with varying concentrations of 2%, 4%, and 6%. The data obtained were analyzed using One Way Anova with a 95% confidence level. The results showed that the use of HPMC as a gelling agent affected pH, viscosity, adhesion, and spreadability but had no effect on other physical tests. The best formula was produced by formula II with a 2% HPMC concentration with the best physical properties.